Estudo da alteração na absorção da luz monocromática (transmitância) como parâmetro de contaminação do mar por hidrocarbonetos - Sieczka Junior, Edson Luiz (2013)
The real time monitoring of seawater in critical environments such as ports entrances and navigation channels is needed in order to avoid major contaminations of the marine environment especially in coastal regions. The most recurrent contamination is hydrocarbon spills. A real time contamination indicator enables immediate action from the responsible sectors. Such measurement might prevent impurities from spreading into a greater area, resulting in faster and more effective cleaning and decontamination process. This study aims to detect changes in the physical behavior of the sea water when hydrocarbon contamination exists. The physical parameter under study is the variation in the transmittance curve of seawater, with specific wavelengths, when there is contamination in the sample. The absorption variation of the electromagnetic wave detected by the photo sensor can indicate that the water sample is contaminated by hydrocarbons. The base equipment for collecting data from the transmittance curves is the spectrophotometer, which is able to perform a scan on an electromagnetic wavelength range between 190 nm to 1100 nm. Two methods were performed using the same radiation source, the first one with horizontal light incidence into the water sample (near-surface) and the second one with vertical incidence, subjecting radiation to absorption caused by the water column and contaminant (gasoline and kerosene). The results obtained in this study show a significant decrease of transmittance in function of the increase in concentration of pollutant (hydrocarbon) in the water, in the more relevant ranges of each substance, with their different molecular structures. The hydrocarbon used in the evaluation of both methods validation was gasoline. The spectrum point of greater sensitivity in measuring the hydrocarbon transmittance is in 360 nm. Using the Lambert-Beer law it was calculated exponential correlation of points obtained with a specific wavelength, in 360 nm this correlation is greater than 99%. The method and results raised enabled the development and application of an optical sensor for sensing seawater according to the variation of light absorption in function of the increasing contaminants concentration (hydrocarbons), and using the Lambert-Beer law to estimating the concentration of product in water.